2009
DOI: 10.1007/s11106-009-9124-9
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature and electrochemical oxidation of transition metal silicides

Abstract: 546.281:541.138 High-temperature and electrochemical oxidation of transition metal silicides, which are widely used in microelectronics as ohmic contacts and protective coatings for high-temperature alloys, are discussed in this review. The process of oxide film formation during annealing or anodizing is extremely important for both applications of silicides. It is discussed for three disilicides: MoSi 2 , WSi 2 , and TiSi 2 . It has been shown that different types of oxide films may form on the disilicide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…In addition, Si element is still present in these domains based on Figure C. It has been reported that transition metal silicides have strong corrosion resistance by forming a protective SiO 2 layer at high temperatures . Thus, a small amount of SiO 2 phase is attached to the surface of the silicides for the water vapor‐treated NFA‐SiC samples.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, Si element is still present in these domains based on Figure C. It has been reported that transition metal silicides have strong corrosion resistance by forming a protective SiO 2 layer at high temperatures . Thus, a small amount of SiO 2 phase is attached to the surface of the silicides for the water vapor‐treated NFA‐SiC samples.…”
Section: Resultsmentioning
confidence: 88%
“…It has been reported that transition metal silicides have strong corrosion resistance by forming a protective SiO 2 layer at high temperatures. [46][47][48] Thus, a small amount of SiO 2 phase is attached to the surface of the silicides for the water vapor-treated NFA-SiC samples. The SiC matrix has O element based on Figure 2E, and Si and C elements based on Figure 2C,D.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results can be clearly seen for these composites as well. It is determined that only W 5 Si 3 secondary phase formed in all three composites after sintering, since WSi 2 also has a high‐temperature oxidation process similar to MoSi 2 . This formation was explained differently by the decomposition of WSi 2 into W 5 Si 3 and Si during hot isostatic pressing at 1500°C and 196 MPa .…”
Section: Resultsmentioning
confidence: 94%
“…By this way, it was determined that rates of the formation of secondary phases (vol% per hour) highly decreased in all composites except for the MoSi 2 –ZrO 2 after annealing for 24 hours, as presented in the Table , indicating their improved thermal stability over time. However, it is important to point out that high fractions of secondary W 5 Si 3 phase up to 38.8 vol% may cause serious issues in real applications under air atmosphere due to its low oxidation resistance . Therefore, MoSi 2 ‐based composites are found to be more thermally stable with the formation of low fractions of Mo 5 Si 3 having reasonable high‐temperature oxidation resistance, and hence, to be more suitable for advanced sensing applications at high temperature and harsh environments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation